Prevalence of post traumatic stress disorder and its predictors among road traffic accident survivors - Khurshid, Amna; Saleem, Yousaf; Ahmad, Saish; Saif Khan, Abdullah; Ayoub, Kashif; Shamsher, Muhammad Faisal; Khan, Tayyab Mumtaz; Ibrahim, Hamza; Hassan, Muhammad; Ahmad, Muhammad Hassan (International Journal Of Community Medicine And Public Health, 2024)
Background: Post-traumatic stress disorder (PTSD) among road traffic accident (RTA) survivors, gets received little attention as medical experts prioritize treating physical injuries. In Pakistan, PTSD remains understudied. Therefore, this study aimed to determine the prevalence and predictors of PTSD. Methods: This cross-sectional study was performed among 128 survivors of RTA at Benazir Bhutto hospital, Rawalpindi. Data were collected via a pre-tested PTSD checklist-specific version (PCL-S) tool to screen for PTSD and a self-designed proforma. Descriptive and inferential statistics were used in the data analysis using the statistical package for the social sciences (SPSS) version 25. The p<0.05 was used set a significant. Results: The 34 (26.56%) participants of study population had PTSD. Following adjustment for potential confounding variables, the following factors were found to be significant predictors of PTSD: time since RTA (1-3 months) (AOR=0.38; 95% CI (0.18, 0.76), history of prior RTA (AOR=2.56; 95% CI (1.22, 5.47), presence of close one in the same RTA, (AOR=2.23, 95% CI (1.14, 4.46), witnessing of death of close one in the same RTA, (AOR=7.49, 95% CI (3.16, 14.68) and previous history of psychiatric illness (AOR=12.35, 95% CI (5.32, 28.29). Conclusions: Our study population had significant prevalence of PTSD (26.56%). Significant predictors of PTSD included the amount of time after the accident, the history of prior traffic accidents, presence of close one in same accident, witnessing the death of close one in same accident, and history of psychiatry disorder.